An assessment of contaminations levels of source and tap water in light of the new EU Directive 2020/2184 - Halina Urbańska-Kozłowska; Małgorzata Wolska; Anna Solipiwko-Pieścik (Desalination and Water Treatment)
Providing healthy and safe water to consumers is a great challenge and responsibility for water supply companies supplying water intended for consumption. Changing legal requirements oblige them to adapt and possibly expand treatment processes to ensure these requirements. A key aspect of ensuring legal requirements and safe water for consumption to consumers is the identification of pollutants, especially micropollutants in water taken for treatment. The studies included monitoring of micropollutants such as pesticides, perfluorinated acids, microplastics, microcystin, PAHs in surface and infiltration water taken for treatment in water treatment plants WTP1 and WTP2, which are the source of drinking water for one of the agglomerations in Poland. In turn, the analysis of the quality of treated water allowed for the assessment of the effectiveness of conventional water treatment processes from monitored pollutants in the tested treatment systems and the assessment of the risks that the presence of these micropollutants in the tested waters carries.